The Relationship Between Anti-Tuberculosis Drug Therapy and Uric Acid and Creatinine Levels in Tuberculosis Patients in Kayong Utara District - Selvianty Selvianty; Ratih Indrawati; Maulidiyah Salim (MEDICA (International Medical Scientific Journal), 2025)
Pulmonary tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis. TB treatment involves five essential drugs: isoniazid, streptomycin, ethambutol, rifampicin, and pyrazinamide. Among these, pyrazinamide and ethambutol are known to potentially increase uric acid and creatinine levels as side effects. This study aimed to examine the relationship between anti-TB drug (OAT) therapy and levels of uric acid and creatinine in TB patients in Kayong Utara District. Using a cross-sectional design and purposive sampling, data were collected from 31 TB patients across three community health centers with the highest TB incidence. Results showed that 54.8% of patients had elevated uric acid levels, while 45.2% had normal levels. For creatinine, 93.5% had normal levels, and 6.5% had elevated levels. Chi-square analysis indicated a significant association between OAT therapy and uric acid levels (p = 0.045), but no significant relationship was found with creatinine levels (p = 1.000). These findings suggest that OAT therapy may affect uric acid levels in TB patients, highlighting the need for monitoring during treatment.